Risk Management for PMO Transformation in Indonesian State-Owned Construction Enterprises - Nisrina, Dhia Tsuraya; Latief, Yusuf; Veronika, Alin (Journal of Project Management Research, 2025)
This research investigates the critical issue of risk management during Project Management Office (PMO) transformation within the Indonesian State-Owned Enterprise construction industry. The study employs a quantitative methodology to identify key risks that impede effective PMO implementation and to evaluate potential mitigation strategies. Survey data, gathered from a diverse sample of construction professionals in state-owned enterprises are analyzed to establish risk profiles and inform evidence-based recommendations. The findings highlight that operational and policy risks are paramount, emphasizing the importance of standardized processes, clear communication channels, and well-defined governance structures. Results further indicate that effective risk management requires tailored strategies that align with the unique characteristics of the organization and the project portfolio. Key strategies include strong leadership support, a robust change management process, and the alignment of PMO objectives with broader business goals. These results are related to previous research and recommendations based on data analysis, but future research with deep dives into the cases and other type of companies are also proposed. This research contributes to a more nuanced understanding of PMO transformation within a developing economy and provides actionable insights for construction industry stakeholders seeking to enhance project outcomes, improve organizational efficiency, and achieve sustainable development goals.